Lessons Learned From Digital Inclusion Initiatives in Rural Communities - Julianna Nieuwsma; Leslie E. Cofie; Abby J. Schwartz; Alice R. Richman; Nate Mizell; Leslie Sanchez (Health Promotion Practice, 2026)
As researchers, policymakers, and community organizations continue to invest in digital inclusion initiatives in rural communities, it is important for stakeholders to build upon past efforts to enhance what has been effective and address previous challenges. The purpose of our study is to highlight and document community-based digital inclusion efforts in rural communities and to discuss the essential lessons learned from these implementation efforts to guide future digital inclusion projects in rural settings. Qualitative interviews were conducted with 15 key informants who have ties to rural communities and knowledge and experience with digital inclusion efforts. This included 10 library staff members and 5 community leaders living, working, and/or serving in Eastern North Carolina (ENC) rural counties. Thematic analysis was used to analyze interview data. Three key themes emerged regarding the digital inclusion efforts occurring in these communities. Themes included (a) Community-based digital inclusion efforts either past or present, (b) Library-based internet connection, and (c) Challenges in implementing digital inclusion efforts. Grassroots efforts in ENC rural communities have provided essential digital inclusion resources and services to community members. These endeavors play a critical role in closing both the digital divide and the health care divide experienced by rural residents. However, finding ways to sustain these efforts remains challenging and needs to be addressed by future researchers alongside local leaders and community members.